On the numerical solution of the three-dimensional advection-diffusion equation - Prusov, V.; Doroshenko, A.; Faragó, I.; Havasi, Á. (Інститут програмних систем НАН України, 2006)
A new approach is proposed for the numerical solution of three-dimensional advection-diffusion equations, which arise, among others, in air pollution modelling. The technique is based on directional operator splitting, which results in one-dimensional advection-diffusion equations. Then upstream-type difference approximations are applied for the first-order derivatives and non-standard difference approximations for the second-order derivatives. This approach leads to significant qualitative improvements in the behaviour of the numerical solutions.